2014
DOI: 10.1021/nl503879a
|View full text |Cite
|
Sign up to set email alerts
|

Hanoi Tower-like Multilayered Ultrathin Palladium Nanosheets

Abstract: This paper describes the synthesis, formation mechanism, and mechanical property of multilayered ultrathin Pd nanosheets. An anisotropic, Hanoi Tower-like assembly of Pd nanosheets was identified by transmission electron microscopy and atomic force microscopy (AFM). These nanosheets may contain ultrathin Pd layers, down to single unit cell thickness. Selected area electron diffraction and scanning transmission electron microscopy data show the interconnected atomically thick layers stacking vertically with rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 78 publications
(108 reference statements)
0
102
0
Order By: Relevance
“…Therefore, the formation of PdCu alloy could be explained by the noble metal‐induced reduction mechanism . Based on this mechanism, Pd(II) was first reduced by Mo(CO) 6 . The resulting Pd atoms then catalyzed the reduction of Cu(II), leading to the formation of small PdCu clusters .…”
Section: Summary Of Cu/pd Atomic Ratios In Different Pdcu Alloy Nanosmentioning
confidence: 99%
“…Therefore, the formation of PdCu alloy could be explained by the noble metal‐induced reduction mechanism . Based on this mechanism, Pd(II) was first reduced by Mo(CO) 6 . The resulting Pd atoms then catalyzed the reduction of Cu(II), leading to the formation of small PdCu clusters .…”
Section: Summary Of Cu/pd Atomic Ratios In Different Pdcu Alloy Nanosmentioning
confidence: 99%
“…2 There are a few studies aimed to synthesis ultra thin metallic materials. For instance Duan et al 4 reported fabrication of poly-supported single-layered rhodium nanosheets using a facile solvothermal method, and Yin et al 5 studied the synthesis, formation mechanism, and mechanical property of multilayered ultrathin palladium nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…Biosynthesized metal nanoparticles have a combination of the two complementary properties: the inorganic properties like mechanical/thermal/structural stability and the properties of organic pendant moieties such as flexibility in solution (like homogeneous catalysts) and therefore, high reactivity of the catalyst . Cross‐coupling reactions have been used as powerful and useful synthetic tools in novel synthetic chemistry . The formation of C − S bonds is momentous in synthetic organic chemistry for the structure of different synthetics, a large number of drugs for diseases such as diabetes, cancer, Alzheimer's, Parkinson's, or inflammatory HIV diseases, and natural biologically active compounds (Figure ) …”
Section: Introductionmentioning
confidence: 99%
“…[40] Cross-coupling reactions have been used as powerful and useful synthetic tools in novel synthetic chemistry. [5,[41][42][43] The formation of C − S bonds is momentous in synthetic organic chemistry for the structure of different synthetics, a large number of drugs for diseases such as diabetes, cancer, Alzheimer's, Parkinson's, or inflammatory HIV diseases, and natural biologically active compounds ( Figure 1). [44][45][46] Recently, aryl sulfides and their derivatives have drawn much attention in molecular precursors for the development of this materials because of their biological, pharmaceutical properties.…”
Section: Introductionmentioning
confidence: 99%